Perpindahan Panas Pada Packed Bed:Konduktivitas Panas Efektif Dan Koefisien Perpindahan Panas Pernukaan Dinding - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Heat transfer in packed beds was studied by flowing air through a tube filled with spherical steel and glass particles, while steam as a heat source was flown through the jacked. It was assumed that the fluid temperature were equal to that of the solid particles (pseudo-homogeneous model). The bed temperatures at various height and radii were measured for various air flow rate and particles size. The mathematical model was solved numerically. Based on the experimental data and the mathematical model proposed, the heat transfer parameters, which were effective thermal conductivity (k,) and heat transfer coefficient on the surface wall (h,â), were evaluated by numerical least squares. The mathematical model turned out to be able to simulate the heat transfer process. The empirical equation was developed to correlate the Reynolds number and the ratio of particles diameter to the ratio of effective thermal conductivity to gas conductivity, and to the Nusselt number.